Aristotle's Hylomorphism: The Causal-Explanatory Model. (21st May 2018) - Peramatzis, Michail
There are several innocuous or trivial ways in which to explicate Aristotle's hylomorphism. For example: objects (or kinds of object) are characterisable in terms of matter and form; or analysable into matter and form; or understood on the basis of matter and form. Serious problems arise when we seek to specify the sorts of relation holding among the different contributors to the hylomorphic picture. Here are some central general questions: What types of relation are most suitable for each n-tuple of contributors (e.g., identity, part-whole, or some other relation)? What direction and modal profile should each relation have (e.g., is form prior to matter and the compound, or is the compound prior to matter and form; is matter essentially or contingently related to form)? In addressing such questions we find that the types, directions, or modal character of the relations that we or Aristotle may favour are often in tension with each other, or clearly lead to inconsistencies. The paper focuses on the Modal Question (M), also known as 'Ackrill's problem': is form essentially or contingently related to matter? I outline a hylomorphic model, what I label the 'causal-explanatory' model (CEM), and show how it can tackle M.